Professional English for Electrical Power Engineering. Part 1. Power Station электронный курс - Ufa, R. A. specialist in the field of electric power engineering Associate Professor of Tomsk Polytechnic University, Candidate of Technical Sciences 1988- (TPU Moodle, 2021)
This course provides the foundation for subsequent courses in electrical engineering and prepares students to apply circuits analysis and related laboratory techniques in advanced research and professional practice. Course objectives: to present a comprehensive and rigorous treatment of electrical engineering fundamentals. Major topics include: DC and AC circuits analysis; sinusoids and phasors; transients; frequency response; nonlinear circuits; rectifiers; three-phase power; Y - ? relationships; and introduction to semiconductor devices. This course provides the foundation for subsequent courses in electrical engineering and prepares students to apply circuits analysis and related laboratory techniques in advanced research and professional practice. Course objectives: to present a comprehensive and rigorous treatment of electrical engineering fundamentals. Major topics include: DC and AC circuits analysis; sinusoids and phasors; transients; frequency response; nonlinear circuits; rectifiers; three-phase power; Y - ? relationships; and introduction to semiconductor devices.